Faithfluencers and Digital Piety: Redefining Religious Authority Among Generation Z - Rizkiyah Hasanah; Zohaib Hassan Sain Baharun (ADPISI (Asosiasi Dosen Pendidikan Agama Islam Se-Indonesia), 2025)
This research is motivated by the emergence of the faithfluencer phenomenon as a new religious authority figure in the digital era that significantly shapes the religious mindset and practices of Generation Z. This change marks a shift from traditional religious authority to a more interactive and contextual, and media-based digital authority. The purpose of this study is to analyze the role of faithfluencers in shaping digital piety and redefining religious authority among Generation Z through social media. This study uses a qualitative approach with descriptive analysis through observation of content on Instagram and TikTok platforms, as well as interviews with active followers. The results show that faithfluencers function not only as conveyors of da'wah messages, but also as social and spiritual mediators who combine religious values with a popular communication style. The digital piety produced through this interaction tends to be reflective, participatory, and experiential, emphasizing personal meaning-making rather than rigid doctrinal transmission. The contribution of this research lies in developing the concept of digital religious authority that is adaptive to the spiritual needs of the younger generation and serves as a strategic reference for religious institutions in optimizing social media-based da'wah that is relevant to the dynamics of today's digital culture.